Hirarki Kebutuhan Abraham Maslow Dalam Proses Pembelajaran Seni Karawitan di SMP Negeri 1 Kubutambahan - Dana, I Komang Restika; Ardini, Ni Wayan; Sustiawati, Ni Luh (STKIP AGAMA HINDU SINGARAJA, 2024)
Motivation can influence human behavior in ways such as increasing enthusiasm, passion, and fulfilling one's own needs to achieve certain goals. Needs at the lowest level are physiological needs, while needs at the highest level are self-actualization needs proposed by Abraham Maslow in his hierarchy of needs theory. The results of this research are that the needs of students are met in the process of learning musical arts in extracurricular karawitan activities at SMP Negeri 1 Kubutambahan, namely: (1) Physiological needs; (2) Security needs; (3) The need for belonging and affection; (4) Reward needs; and (5) Self-actualization needs. This research was designed using qualitative research methods with Abraham Maslow's motivation theory approach and an analytical descriptive approach, meaning that the results of the discussion in this research are described in the form of words or sentences according to data that has been obtained from various sources. The data collection method used was complete participant observation.